(untitled) (England, 1971)
This comprehensive collection presents organization theory in its historical context. It includes an authoritative selection of seminal articles published since the 1960s, which exercise continuing influence on contemporary thinking about organizations.
Keywords: Tổ chức xã hội,Organizational behavior